Non-invasive Evaluation of Electromechanical Transmission in Patients with Hypertensive Response to Exercise Stress Test - Ahmet Ferhat KAYA; Mehmet Hasan OZDIL; Cemalettin YILMAZ; Raif KILIC; Mehmet OZBEK; Hasan KAYA (Medeniyet Medical Journal)
Objective: Excessive hypertensive response to exercise testing is associated with adverse cardiovascular events such as left ventricular hypertrophy and atrial fibrillation (AF). In this study, we examined the relationship between electromechanical delay and excessive hypertensive response to exercise testing. Methods: Twenty-five people who had a hypertensive response to the exercise stress test and 28 people who were similar in age and gender with a normal blood pressure response in the exercise stress test as the control group were included in the study. Results: There was no statistical difference between the study groups in blood pressure holter values, conventional echocardiography findings, and exercise stress test findings. Lateral PA-TDI time (the time from the beginning of the P wave measured by tissue Doppler imaging to the beginning of the A' wave), left atrial electromechanical delay, and interatrial electromechanical delay were observed to be significantly longer in the hypertensive response group to exercise stress test compared with the control group (74.0+-6.3 vs. 68.8+-5.7, p=0.003; 24.7+-7.0 vs. 19.6+-7.1, p=0.013; 36.8+-8.5 vs. 30.6+-6.6, p=0.003, respectively). Conclusions: Early detection of electromechanical delay non-invasively may be useful in this patient group in predicting the development of new AF risk.